2019
DOI: 10.1002/jrs.5744
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two‐dimensional materials from Raman spectral data

Abstract: Two-dimensional materials like graphene and transition metal dichalcogenides materials such as WS 2 and MoS 2 are an attractive material platform for optoelectronics devices, photovoltaics, and strain-induced deterministic singlephoton sources due to high carrier mobility, tunable band gap, and ease of transfer on the desired substrates. In many of these applications, knowing the number of layers is important; for example, only strained monolayer of WSe 2 emits single photons at 4.5 K. Here, we present an anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 83 publications
0
1
0
Order By: Relevance
“…Raman spectroscopy is an optical spectroscopic method that has been extensively used in the characterization of materials. A study reported a combination of computational intelligence made the analysis easier, where the input parameters are the major concern from which the number of layers can be easily estimated [106] and this analysis can provide the information on nature and the number of defects present in the sample and the intensity of these peaks reveals the nature and the number of defects [107]. The downward shift of the G-band in nitrogen and boron-doped graphene quantum dots than undoped GQDs reveal that the dopants are n-type [87] and in N-GQDs it was observed that there is a higher broadness in the D band than GQDs representing some disorderliness in the structure [108].…”
Section: Defects Characterization 41 Raman Spectroscopymentioning
confidence: 99%
“…Raman spectroscopy is an optical spectroscopic method that has been extensively used in the characterization of materials. A study reported a combination of computational intelligence made the analysis easier, where the input parameters are the major concern from which the number of layers can be easily estimated [106] and this analysis can provide the information on nature and the number of defects present in the sample and the intensity of these peaks reveals the nature and the number of defects [107]. The downward shift of the G-band in nitrogen and boron-doped graphene quantum dots than undoped GQDs reveal that the dopants are n-type [87] and in N-GQDs it was observed that there is a higher broadness in the D band than GQDs representing some disorderliness in the structure [108].…”
Section: Defects Characterization 41 Raman Spectroscopymentioning
confidence: 99%
“…By the types of Raman modes, the interactions in TMDs can be analyzed qualitatively and even quantitatively. [30][31][32][33] In the first publication, in the theory of alloyed crystals, Martin [34] proposed a simple model to describe the relative intensity of Raman scattering in alloyed crystals with the two-mode behavior. The local susceptibility, both linear and nonlinear, was assumed to be a sum of concentration-independent atomic contributions.…”
Section: Introductionmentioning
confidence: 99%